Porangisasi Pemberdayaan Petani Melalui Metode Indirect Intervention di Ponorogo - Pajar Hatma Indra Jaya; Matsna Naqilal Khidhriyah (Jurnal Nuansa Akademik, 2022)
The farmer is the most common occupation in Indonesia, but farmers are associated with poverty. Empowerment of farmers is important, but finding out the effectiveness of empowerment method is not easy. In Ponorogo Regency, a unique phenomenon occurred, some farmers became rich and economically successful. This paper aims to explain how the empowerment method is carried out for farmers in Ponorogo Regency, so that they become successful. To answer this question, the researchers conducted observations, documentation, and interviews to twelve informants. This paper finds out successful farmers in Ponorogo is not due to empowerment programs that are directly given to farmers, but indirect intervention. Indirect intervention is carried out in the form of disseminating information about success that inspires other farmers to imitate and government intervention to keep market prices attractive.